Magnetic properties of optimized cobalt nanospheres grown by focused electron beam induced deposition (FEBID) on cantilever tips - Sangiao, Soraya; Magén, César; Mofakhami, Darius; de Loubens, Grégoire; De Teresa, José María (Beilstein Journal of Nanotechnology, 2017)
In this work, we present a detailed investigation of the magnetic properties of cobalt nanospheres grown on cantilever tips by focused electron beam induced deposition (FEBID). The cantilevers are extremely soft and the cobalt nanospheres are optimized for magnetic resonance force microscopy (MRFM) experiments, which implies that the cobalt nanospheres must be as small as possible while bearing high saturation magnetization. It was found that the cobalt content and the corresponding saturation magnetization of the nanospheres decrease for nanosphere diameters less than 300 nm. Electron holography measurements show the formation of a magnetic vortex state in remanence, which nicely agrees with magnetic hysteresis loops performed by local magnetometry showing negligible remanent magnetization. As investigated by local magnetometry, optimal behavior for high-resolution MRFM has been found for cobalt nanospheres with a diameter of ≈200 nm, which present atomic cobalt content of ≈83 atom % and saturation magnetization of 106 A/m, around 70% of the bulk value. These results represent the first comprehensive investigation of the magnetic properties of cobalt nanospheres grown by FEBID for application in MRFM.
Keywords: cobalt nanostructures; electron holography; focused electron beam induced deposition; magnetic deposits; magnetic resonance force microscopy

(untitled) - De Teresa, J. M.; Fernández-Pacheco, A. (Appl. Phys. A, 2014)

(untitled) - De Teresa, J. M.; Fernández-Pacheco, A.; Córdoba, R.; Serrano-Ramón, L.; Sangiao, S.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2016)

(untitled) - Boero, G.; Utke, I.; Bret, T.; Quack, N.; Todorova, M.; Mouaziz, S.; Kejik, P.; Brugger, J.; Popovic, R. S.; Hoffmann, P. (Appl. Phys. Lett., 2005)

(untitled) - Gabureac, M.; Bernau, L.; Utke, I.; Boero, G. (Nanotechnology, 2010)

(untitled) - Serrano-Ramón, L.; Córdoba, R.; Rodríguez, L. A.; Magén, C.; Snoeck, E.; Gatel, C.; Serrano, I.; Ibarra, M. R.; De Teresa, J. M. (ACS Nano, 2011)

(untitled) - Córdoba, R.; Lavrijsen, R.; Fernández-Pacheco, A.; Ibarra, M. R.; Schoenaker, F.; Ellis, T.; Barcones-Campo, B.; Kohlhepp, J. T.; Swagten, H. J. M.; Koopmans, B.; Mulders, J. J. L.; De Teresa, J. M. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Lau, Y. M.; Chee, P. C.; Thong, J. T. L.; Ng, V. (J. Vac. Sci. Technol., A, 2002)

(untitled) - Utke, I.; Hoffmann, P.; Berger, R.; Scandella, L. (Appl. Phys. Lett., 2002)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Wachter, S.; Shawrav, M. M.; Persson, A.; Gunnarsson, K.; Svedlindh, P.; Stöger-Pollach, M.; Bertagnolli, E. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Belova, L. M.; Hellwig, O.; Dobisz, E.; Dahlberg, E. D. (Rev. Sci. Instrum., 2012)

(untitled) - Lavenant, H.; Naletov, V.; Klein, O.; de Loubens, G.; Casado, L.; De Teresa, J. M. (Nanofabrication, 2014)

(untitled) - Fernández-Pacheco, A.; De Teresa, J. M.; Córdoba, R.; Ibarra, M. R.; Petit, D.; Read, D. E.; O’Brien, L.; Lewis, E. R.; Zeng, H. T.; Cowburn, R. P. (Appl. Phys. Lett., 2009)

(untitled) - Idigoras, O.; Nikulina, E.; Porro, J. M.; Vavassori, P.; Chuvilin, A.; Berger, A. (Nanofabrication, 2014)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Belić, D.; Bertagnolli, E. (ACS Nano, 2013)

(untitled) - Sharma, N.; van Mourik, R. A.; Yin, Y.; Koopmans, B.; Parkin, S. S. P. (Nanotechnology, 2016)

(untitled) - De Teresa, J. M.; Córdoba, R. (ACS Nano, 2014)

(untitled) - Dobrovolskiy, O. V.; Begun, E.; Huth, M.; Shklovskij, V. A.; Tsindlekht, M. I. (Physica C, 2011)

(untitled) - Fernández-Pacheco, A.; Serrano-Ramón, L.; Michalik, J. M.; Ibarra, M. R.; De Teresa, J. M.; O’Brien, L.; Petit, D.; Lee, J.; Cowburn, R. P. (Sci. Rep., 2013)

(untitled) - Franken, J. H.; van der Heijden, M. A. J.; Ellis, T. H.; Lavrijsen, R.; Daniels, C.; McGrouther, D.; Swagten, H. J. M.; Koopmans, B. (Adv. Funct. Mater., 2014)

(untitled) - Vavassori, P.; Pancaldi, M.; Perez-Roldan, M. J.; Chuvilin, A.; Berger, A. (Small, 2016)

(untitled) - Lapicki, A.; Kang, K.; Suzuki, T. (IEEE Trans. Magn., 2002)

(untitled) - Ervin, M. H.; Nichols, B. M. (J. Vac. Sci. Technol., B, 2009)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Belic, D.; Shawrav, M. M.; Persson, A.; Gunnarsson, K.; Svedlindh, P.; Bertagnolli, E. (Phys. Status Solidi A, 2014)

(untitled) - Tu, F.; Drost, M.; Vollnhals, F.; Späth, A.; Carrasco, E.; Fink, R. H.; Marbach, H. (Nanotechnology, 2016)

(untitled) - Pohlit, M.; Porrati, F.; Huth, M.; Ohno, Y.; Ohno, H.; Müller, J. (J. Appl. Phys., 2015)

(untitled) - Fernández-Pacheco, A.; Serrano-Ramón, L. E.; Tyliszczak, T.; Chou, K. W.; Córdoba, R.; Szkudlarek, A.; Brien, L. O.; Kapusta, C.; Ibarra, M. R.; De Teresa, J. M. (Nanotechnology, 2012)

(untitled) - Sangiao, S.; Morellón, L.; Ibarra, M. R.; De Teresa, J. M. (Solid State Commun., 2011)

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Stanford, M. G.; Plank, H.; Rack, P. D. (ACS Nano, 2016)

(untitled) - Silvis-Cividjian, N.; Hagen, C. W.; Kruit, P. (J. Appl. Phys., 2005)

(untitled) - Bernau, L.; Gabureac, M.; Erni, R.; Utke, I. (Angew. Chem., Int. Ed., 2010)

(untitled) - Pablo-Navarro, J.; Sanz-Hernández, D.; Magén, C.; Fernández-Pacheco, A.; de Teresa, J. M. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Peinado, P.; Sangiao, S.; De Teresa, J. M. (ACS Nano, 2015)

(untitled) - Fernández-Pacheco, A.; De Teresa, J. M.; Córdoba, R.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Córdoba, R.; Sharma, N.; Kölling, S.; Koenraad, P. M.; Koopmans, B. (Nanotechnology, 2016)

(untitled) - Córdoba, R.; Sesé, J.; De Teresa, J. M.; Ibarra, M. R. (Microelectron. Eng., 2010)

(untitled) - Mulders, J. J. L.; Belova, L. M.; Riazanova, A. (Nanotechnology, 2010)

(untitled) - Gazzadi, G. C.; Mulders, J. J. L.; Trompenaars, P.; Ghirri, A.; Rota, A.; Affronte, M.; Frabboni, S. (Microelectron. Eng., 2011)

(untitled) - Begun, E.; Dobrovolskiy, O. V.; Kompaniiets, M.; Sachser, R.; Gspan, C.; Plank, H.; Huth, M. (Nanotechnology, 2015)

(untitled) - Puydinger dos Santos, M. V.; Velo, M. F.; Domingos, R. D.; Zhang, Y.; Maeder, X.; Guerra-Nuñez, C.; Best, J. P.; Béron, F.; Pirota, K. R.; Moshkalev, S.; Diniz, J. A.; Utke, I. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Schirmer, M.; Walz, M.-M.; Papp, C.; Kronast, F.; Gray, A. X.; Balke, B.; Cramm, S.; Fadley, C. S.; Steinrück, H.-P.; Marbach, H. (Nanotechnology, 2011)

(untitled) - Sidles, J. A.; Garbini, J. L.; Bruland, K. J.; Rugar, D.; Züger, O.; Hoen, S.; Yannoni, C. S. (Rev. Mod. Phys., 1995)

(untitled) - Degen, C. L.; Poggio, M.; Mamin, H. J.; Rettner, C. T.; Rugar, D. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Lee, I.; Obukhov, Y.; Xiang, G.; Hauser, A.; Yang, F.; Banerjee, P.; Pelekhov, D. V.; Hammel, P. C. (Nature, 2010)

(untitled) - Naletov, V. V.; de Loubens, G.; Albuquerque, G.; Borlenghi, S.; Cros, V.; Faini, G.; Grollier, J.; Hurdequint, H.; Locatelli, N.; Pigeau, B.; Slavin, A. N.; Tiberkevich, V. S.; et al. (Phys. Rev. B, 2011)

(untitled) - Guo, F.; Belova, L. M.; McMichael, R. D. (Phys. Rev. Lett., 2013)

(untitled) - Mamin, H. J.; Rettner, C. T.; Sherwood, M. H.; Gao, L.; Rugar, D. (Appl. Phys. Lett., 2012)

(untitled) - Mamin, H. J.; Rugar, D. (Appl. Phys. Lett., 2001)

(untitled) - Hickman, S. A.; Moore, E. W.; Lee, S.; Longenecker, J. G.; Wright, S. J.; Harrell, L. E.; Marohn, J. A. (ACS Nano, 2010)

(untitled) - Klein, O.; de Loubens, G.; Naletov, V. V.; Boust, F.; Guillet, T.; Hurdequint, H.; Leksikov, A.; Slavin, A. N.; Tiberkevich, V. S.; Vukadinovic, N. (Phys. Rev. B, 2008)

(untitled) - Pablo-Navarro, J.; Magén, C.; de Teresa, J. M. (Nanotechnology, 2016)

(untitled) - Snoeck, E.; Gatel, C.; Lacroix, L. M.; Blon, T.; Lachaize, S.; Carrey, J.; Respaud, M.; Chaudret, B. (Nano Lett., 2008)